The Effects Of Intellectual Capital And Job Satisfaction On Employee Work Productivity At PT. Bank Mandiri Taspen Gorontalo Sub-Branch Office - Rahmisyari Rahmisyari; Musafir Musafir (Brilliant International Journal Of Management And Tourism, 2023)
This study aims to determine how much influence intellectual capital (X1) and job satisfaction (X2) have on work productivity (Y) at Bank Mandiri Taspen Supporting Branch Offices (KCP) Gorontalo. The sampling technique used in this study was simple random sampling, while the main data collection was through a list of statements that were tested through validity and reliability tests. The technique used for analysis is path analysis. The results of hypothesis testing show that simultaneously, intellectual capital (X1) and work satisfaction (X2) have an effect on employee work productivity at the Bank Mandiri Taspen Gorontalo Sub-Branch Office, which is equal to 0.741 or 74.1%. The results of partial hypothesis testing of intellectual capital (X1) have an effect on employee work productivity (Y) PT. Bank Mandiri Taspen Gorontalo Sub-Branch Office, which is equal to 0.376, while job satisfaction (X2) partially affects employee work productivity (Y), which is equal to 0.332.